The Effect of Classroom Management and Classroom Climate on Student Engagement in Learning at the MPLB Program at SMK Negeri 16 Jakarta - Cahya Mustika Gandasari; Dewi Nurmalasari; Susan Febriantina (The Future of Education Journal, 2026)
This study was motivated by students’ suboptimal engagement in learning, as evidenced by their low participation in the learning process. This condition is believed to be influenced by classroom management and classroom climate, which are key factors in creating a conducive learning environment. This study aims to analyze the influence of classroom management and classroom climate on student engagement in the Office Management and Business Services (MPLB) program at SMK Negeri 16 Jakarta. The study employs a quantitative approach using a survey method administered to 105 students in grades 10 and 11, selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using validity and reliability tests, classical assumptions, multiple linear regression, t-tests, F-tests, and the coefficient of determination using SPSS. The results of the study indicate that classroom management has a positive and significant effect on student engagement in learning (t-calculated = 4.157; p < 0.05), as does classroom climate (t-calculated = 7.617; p < 0.05). Simultaneously, both variables had a positive and significant effect (F-calculated = 131.308; p < 0.05). The Adjusted R-Square value of 0.714 indicates that 71.4% of the variation in student learning engagement is explained by classroom management and classroom climate, while 28.6% is influenced by other factors outside the research model. These findings underscore the importance of effective classroom management and a conducive classroom climate for enhancing student learning engagement.